Aspiration risk in relation to Glasgow Coma Scale score and clinical parameters in patients with severe acute alcohol intoxication: a single-centre, retrospective study - Conzelmann, Michael; Hoidis, Anne; Bruckner, Thomas; Popp, Erik; Koschny, Ronald (BMJ open, 2021)
Objectives In alcohol intoxicated patients, the decision for or against airway protection can be challenging and is often based on the Glasgow Coma Scale (GCS). Primary aim of this study was to analyse the aspiration risk in relation to the GCS score and clinical parameters in patients with severe acute alcohol monointoxication. Secondary aim was the association between the blood alcohol level and the GCS score. Setting Single-centre, retrospective study of alcoholised patients admitted to a German intensive care unit between 2006 and 2020. Participants A total of n=411 admissions were eligible for our analysis. Clinical measures and analysis The following data were extracted: age, gender, admission time, blood alcohol level, blood glucose level, initial GCS score, GCS score at admission, vital signs, clinical signs of aspiration and airway management measures. The empirical distribution of continuous and categorical data was calculated. Binary multivariable logistic regression analysis was used to identify possible risk factors for aspiration. Results The mean age was 35 years. 72% (n=294) of the admissions were male. The blood alcohol level (mean 2.7 g/L±1.0, maximum 5.9 g/L) did not correlate with the GCS score but with the age of the patient. In univariate analysis, the aspiration risk correlated with blood alcohol level, age, GCS score, oxygen saturation, respiratory rate and blood glucose level and was significantly higher in male patients, on vomiting, and in patients requiring airway measures. Aspiration rate was 45% (n=10) in patients without vs 6% (n=3) in patients with preserved protective reflexes (p=0.0001). In the multivariate analysis, only age and GCS score were significantly associated with the risk of aspiration. Conclusion Although in this single-centre, retrospective study the aspiration rate in severe acute alcohol monointoxicated patients correlates with GCS and protective reflexes, the decision for endotracheal intubation might rather be based on the presence of different risk factors for aspiration.
Gesehen am 10.11.2021